Analisis Implementasi Sistem Meritokrasi Aparatur Sipil Negara (ASN) Pada Pemerintahan Provinsi Sumatera Barat di Biro Xyz - Mutiara Claudia Silitonga; Eka Mariyanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the implementation of the meritocracy system in the management of the State Civil Apparatus (ASN) in the West Sumatra Provincial Government, specifically in the Bureau Xyz. The merit system is one of the main pillars of bureaucratic reform to create a professional, integrity-based, and perormance-oriented apparatus. The research approach uses a qualitative descriptive method with interview, observation, and document review techniques. The results of the study indicate that the implementation of the merit system in the Bureau Xyz has been running relatively well with reference to employee qualifications, competencies, and performance achievements. However, obstacles are still found such as limited human resources, the persistence of old cultural bureaucracy, and uneven implementation across all levels of the organization. These findings are in line with Max Weber's bureaucratic theory which emphasizes the importance of rational rules, clear structures, and the principle of feasibility as the basis for employee management. Therefore, it is necessary to strengthen supervision and leadership so that meritocracy is truly realized consistently.